Energy drinks: is there anything to be concerned about? A review of the literature with attention to the value of drinks among athletes - Witkowska, Maria; Skotnicka, Joanna; Błaszczak, Karolina; Turek, Monika; Jaroń, Aleksandra; Jastrzębska, Katarzyna; Wojciechowska, Klara; Borkowski, Adrian; Sawicki , Mateusz (Quality in Sport, 2024)
Introduction: Popular energy drinks containing caffeine, taurine or guarana are currently generating a lot of interest. Their supply is an increasingly popular method of boosting the body. Therefore, it is important to know the effects of such drinks on health. Objective: A review of the literature on the health effects of energy drinks with a focus on the value of their consumption in athletes. Current Knowledge: Many studies have been made and numerous medical cases have been analyzed to assess the health effects of energy drinks. The most commonly described complications are those involving the cardiovascular and neurological systems, but there are also cases of gastrointestinal, kidney, gynecological or skin diseases. The severity of these complications depends on the amount of energy drinks consumed and the time interval in which they were drunk. Nowadays, athletes are increasingly turning to energy drinks to boost their performance. It is also noticeable that children and adolescents who should not consume caffeine or sugar in excess consume this type of drink. Conclusions: The growing popularity of energy drinks, including among professional athletes as well as children and adolescents, is leading to an increasing number of complications due to their excessive consumption. Therefore, further research on their health effects and harmfulness is needed to determine their safe use.